Beta-2 microglobulin is important for disease progression in a murine model for amyotrophic lateral sclerosis - Staats, Kim A.; Schonefeldt, Susann; Van Rillaer, Marieke; Van Hoecke, Annelies; Van Damme, Philip; Robberecht, Wim; Liston, Adrian; Van Den Bosch, Ludo (Frontiers in Cellular Neuroscience, 2013)
Beta-2 microglobulin (beta2m) is an essential component of the major histocompatibility complex (MHC) class I proteins and in the nervous system beta2m is predominantly expressed in motor neurons. As beta2m can promote nerve regeneration, we investigated its potential role in amyotrophic lateral sclerosis (ALS) by investigating its expression level as well as the effect of genetically removing beta2m on the disease process in mutant SOD1G93A mice, a model of ALS. We observed a strong upregulation of beta2m in motor neurons during the disease process and ubiquitous removal of beta2m dramatically shortens the disease duration indicating that beta2m plays an essential and positive role during the disease process. We hypothesize that beta2m contributes to plasticity that is essential for muscle reinnervation. Absence of this plasticity will lead to faster muscle denervation and counteracting this process could be a relevant therapeutic target.